Effect of the HBV Capsid Assembly Inhibitor Bayer 41-4109 on the Intracellular Localization of EGFP-Core Fusion Proteins - Aris Haryanto; Nastiti Wijayanti; Michael Kann (Indonesian Journal of Biotechnology, 2007)
Bayer 41-4109 is heteroarylpyrimidine (HAP) which has been identified as potent of HBV capsid assembly inhibitor. The present study was to study effect of Bayer 41-4109 treatment on the intracellular localization of EGFP-Core fusion proteins into HepG2 cells. Three recombinant plasmids of pEGFP-Core with single, double and triple NLS of HBV core (EGFP-Core 1C, 2C and 3C ) and two recombinant plasmids with single and triple NLS of SV-40 (EGFP-Core 1 and 3 SV-40) were used in this work. After transient transfected into HepG2 cells and treated with Bayer 41-4109, the intracellular localization of expressed fusion proteins from all plasmid constructions were determined and quantified under confocal laser microscope. Results shown that Bayer 41-4109 treatment in HepG2 cells inhibited the nuclear localization of EGFP-Core with single of triple HBV core NLS. As well as the constructions of expressed fusion protein with single and triple SV-40 NLS (EGFP-Core 1 and 3 SV-40 NLS) showed decreasing the nuclear localization after treated with Bayer 41-4109, even not as strong as EGFP-Core 1C and 3C NLS. Bayer 41-4109 has been identified as a potent inhibitors of HBV replication which has multiple effects on HBV capsid assembly. It may inhibit virus replication by inducing assembly inappropriately and by misdirecting assembly decreasing the stability of normal capsids. Keywords: HBV capsid, Bayer 41-4109, EGFP-Core fusion protein, HepG2 cell